ANALISIS SUMBER ILMU PENGETAHUAN DALAM AYAT ALQURAN (Sebuah Kajian Ontologis) - Ari Khairurrijal Fahmi (Universitas Muhammadiyah Prof Dr Hamka, 2016)
The objective of this research is to acquire deep understanding of the verses of Alquran contained with the theoretical philosopy of sciences, and focus of this research are: the onthological studies of alquran as a bases of sciences..The research method used in this study is a method of analysis with a qualitative approach to content. The approach used in analyzing the content to reveal the verses of Alquran. The research instrument is the researcher himself who is equipped with table analysis. The result showed the various verses of alquran containing the theory of thruthness, the basic of phisics sciences, biologi and Math are there in the Quran.